Evaluation of different green technological approaches for the extraction of oil from grape seeds: A comparative study - M. Ubaid; C.S. Sainia (Grasas y Aceites)
The present study aimed to assess the impact of eco-friendly approaches, including supercritical CO2 (SCO), supercritical CO2+ethanol (SCE), para-cymene (PC), and the cold-press (CP) method on the quality characteristics of grape seed oil (GSO). The results revealed that the PC approach produced the maximum oil yield of 19.46 %, followed by SCE (18.61 %), Hexane (HX) (18.03 %), SCO (16.47 %), and CP (11.01 %). The fatty acid profile and antioxidant activity of SCE oil were superior to all other tested approaches. The total phenolic content (TPC) in the extracted oils ranged from 109.77 mg GAE·kg–1 to 132.01 mg GAE·kg–1, with SCE having the highest TPC and HX having the lowest TPC. PC, SCO, SCE, and CP extracted oils exhibited high total tocopherol contents (TTC) of 233.61, 257.01, 264.26 and 251.89 mg·kg–1 as compared to 214.13 mg·kg–1 in hexane, respectively. The overall findings demonstrate that adopting environmentally sustainable solvents and extraction methods could serve as a preferable alternative to conventional approaches without compromising the quality characteristics of the extracted grape seed oil.